2021
DOI: 10.1021/acs.cgd.1c00055
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Structural Changes Induced by X-ray Nanopatterning via Nano-X-ray Diffraction and Corresponding Electrical Effects

Abstract: We have investigated the modifications induced in high-T c superconductor Bi 2 Sr 2 CaCu 2 O 8+δ (Bi-2212) single crystals by irradiation with an X-ray nanobeam 250 × 250 nm 2 in size with E = 14.85 keV and a time-averaged photon flux Φ 0 = 7.53 × 10 8 ph s −1 . Crystals were mounted onto amorphous substrates with electrical contacts to allow for both X-ray diffraction (XRD) and electrical measurements on the same sample. Changes in the domain structure were monitored via space-resolved nano-XRD mapping, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Poccia et al (Poccia et al, 2011) obtained high-quality superconducting regions in super oxygenated layered cuprate. Truccato et al (Pagliero et al, 2014;Truccato et al, 2016;Rabbani et al, 2021) irradiated Bi2212 microcrystals to fabricate a Josephson device.…”
Section: Oxide Electronic Propertiesmentioning
confidence: 99%
“…Poccia et al (Poccia et al, 2011) obtained high-quality superconducting regions in super oxygenated layered cuprate. Truccato et al (Pagliero et al, 2014;Truccato et al, 2016;Rabbani et al, 2021) irradiated Bi2212 microcrystals to fabricate a Josephson device.…”
Section: Oxide Electronic Propertiesmentioning
confidence: 99%
“…Indeed, some of us have already shown that, using synchrotron radiation nanoprobes with sizes of the order of 50 Â 50 nm 2 and modifying the corresponding photon flux and dose, it is possible to switch from ordinary material characterization to material modification. [21][22][23][24][25][26][27] In the case that a superconducting oxide is irradiated in an approximately uniform way, this treatment corresponds to a variation of its oxygen doping level, [28][29][30] but if only some carefully designed portions are irradiated, a current path can be drawn in the material in such a way to fabricate a Josephson device. [31] Thus, the whole technique can be considered an alternative X-ray nanopatterning (XNP) method to locally introduce defects in oxides and fabricate devices as desired without etching the crystals.…”
mentioning
confidence: 99%